The Role of The Environment and Heritage Language Instructions as an Input Factor in Literacy Development : The Case of Kurdish Bilingual Children in Finland - Goyi, Siddik (My University, 2023)
This master’s thesis is written in the field of language education within the framework of immigrant languages in host countries. It aims to investigate the impacts of the environmental conditions, such as family dynamics, peers, and heritage language instructions (Finnish: Oman äidinkielen opetus) particularly provided in Finnish public schools at the basic education levels (grade 1-8) for the children of Kurdish (Kurmanji) background. The study was initiated on the grounds of the hypothesis that especially the heritage language education of Kurdish children would comprise different pedagogical aspects, and thus, the development of their heritage language also occurs in divergent ways in the diaspora compared to that of other nationalities. To narrow the scope of the research, the impact of the instructions and the effect of the environment was handled primarily from the perspective of literacy skills in the Kurdish Kurmanji dialect. In order to investigate the impact of environmental input on children’s literacy skills, two main dimensions of their linguistic condition needed to be discovered: the amount and the characteristics of the Kurmanji input they receive from their environment and the language proficiency they posses regarding Kurmanji. Therefore, two different data collection tools that could be used for collecting as much data as possible were developed. The first tool was a comprehensive survey that aimed to reveal the linguistic input factors involved in the Kurdish-Kurmanji language development, such as exposure, environment, family construction, etc. The second tool was a literacy test with eight tasks targeting crucial literacy skills such as word recognition, reading comprehension, listening competency, etc. The reason for having two different instruments derived from the need to grasp the relationships between various factors that play a role in language development and preservation within the minority context in the diaspora. The study's results confirm the ´complexities regarding the unique position of the Kurdish language. In more explicit terms, due to a lack of official settings, the literacy skills in Kurmanji are feeble among the families. Therefore, the own-mother language classes in public schools appears not to be the only resource for obtaining literacy for their children. In another word, participating this education was not the variable that contributed the most to all aspects of the literacy skills, except some areas, such as general reading skills. At the same time, children did not show significant performance in other literacy areas, such as vocabulary depth. The results also show deficiencies of linguistic input that these Kurdish families are constrained by and have correlations with the socio-political background of their homeland. For instance, the inadequacy of written materials, poor standardization of the spoken language among the native speakers from different parts of Kurdistan, weak educational levels of the parents in their mother tongue, and other similar determinants negatively affect both literacy and general capabilities in Kurdish. Given that these factors affect parental education and that fathers are relatively more educated in the Kurdish community, the findings indicate that fathers significantly impact their children’s Kurdish literacy skills, even more than the heritage instructions. Apart from these, age was an essential variability in positive correlation with children’s literacy skills. This study reveals numerous factors and variabilities in Finland's Kurdish-backgrounded children's language acquisition and maintenance processes. Therefore, the essential components of this intricate linguistic case were uncovered throughout the present research, and ideas about current limitations and possibilities to enable more comprehensive studies on the subject in the future were aimed to be established.
Keywords: Heritage language instructions, Kurdish language, Kurmanji, Kurdish in Finland, omanäidinkielen opetus